Answer:
The solution was solved correctly by Keith
The solutions of the equation are x=-5,x=-12
Step-by-step explanation:
we have
[tex]x^{2}+17x+72=12[/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]x^{2}+17x=12-72[/tex]
[tex]x^{2}+17x=-60[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side.
[tex]x^{2}+17x+8.5^{2} =-60+8.5^{2}[/tex]
[tex]x^{2}+17x+72.25 =12.25[/tex]
Rewrite as perfect squares
[tex](x+8.5)^{2}=12.25[/tex]
square root both sides
[tex](x+8.5)=(+/-)3.5[/tex]
[tex]x=-8.5(+/-)3.5[/tex]
[tex]x=-8.5(+)3.5=-5[/tex]
[tex]x=-8.5(-)3.5=-12[/tex]
The solution was solved correctly by Keith
The solutions of the equation are x=-5,x=-12